Analisis Perilaku Sosial Santri sebagai Dampak dari Penggunaan Gadget di Pondok Pesantren Manbaul Hikam Desa Tegalmojo Kecamatan Tegalsiwalan Kabupaten Probolinggo - Abd. Azi; Fika Anjana; Ahmad Affani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to look at the phenomenon of gadget use and its impact on the social behavior of children at the Manbaul Hikam Islamic Boarding School in Tegalmojo Village, Tegalsiwalan District, Probolinggo Regency. This type of research is qualitative research with descriptive methods. The selection of informants was carried out using Purposive Sampling technique. The type of data is collected through observation, interviews and documentation. The research results show that some students use gadgets. The features that are often used are camera, WA, games, Mp3, YouTube, internet and social media. These features are used to find the information needed, search for study materials, for entertainment, and to relieve boredom. Gadgets are always used all the time and are often used at inappropriate times, such as in the learning process of students using gadgets without the teacher's knowledge. The phenomenon of using gadgets has an impact on the social behavior of students at the Manbaul Hikam Islamic Boarding School in Tegalmojo Village, namely making it easy for students to interact with many people via social media so that they lose track of time and often do not participate in Islamic Boarding School activities.